Measuring efficiency in transport: the state of the art of applying data envelopment analysis - Markovits-Somogyi, Rita (Transport, 2011)
Data Envelopment Analysis (DEA) is a non-parametric linear programming method used for determining the efficiency of a set of companies as compared to the best practice frontier. It can be employed to analyze private, public or non-profit organizations. The application of the method in the transport sector is wide-spread, especially in the evaluation of airports, ports, railways and urban transport companies. The present paper is aimed at giving a review of how DEA is applied in the transport sector with a special emphasis on the inputs and outputs selected in the DEA models employed in different fields. For this reason, the author has compiled data from 69 DEA applications found or reported in literature, investigated their characteristics and the field of applying them along with the inputs and outputs used. First Published Online: 12 Apr 2011